Classification of time-reversal-invariant crystals with gauge structures - Z. Y. Chen; Zheng Zhang; Shengyuan A. Yang; Y. X. Zhao (Nature Communications, 2023)
Projective representations of crystal symmetries are indispensable for understanding artificial crystals. Here, authors establish a unified theory of projective crystal symmetries with time-reversal invariance, and construct models for all 458 projective symmetry algebras for the 17 two-dimensional wallpaper groups.